PROBLEMATIKA KEPROFESIONALAN GURU SENI RUPA DI SMP N 29 PADANG - Jerry Hakimi, Drs. Jamilus, M. Pd, Dra. Jupriani, M. Pd (Universitas Negeri Padang, 2013)
This study aimed to obtain information and description of: Problems of professionalism art teacher at SMP N 29 Padang that consists of a principal point of view in addressing the problems of understanding and education about law, culture and art teacher effort in sufficient time of certification, how to master the material in Arts Culture clumps, and increase professionalism. While this type of research is qualitative. Sources of data in this study are primary data are taken directly from the sources such as principals and teachers of art and culture through interviews and documentation. While the secondary data in the form of adocument or file that is given directly by the principal and teachers. Kata Kunci : Keprofesionalan seorang guru seni rupa.